Kontaktsoner og grenseområder Interaksjon, konflikt og samarbeid i Norden, Midtøsten og Midtvesten ca. 1520-2020 - Kaveh, Chalak (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
This anthology takes up the subject of border areas and contact zones, both as actual places and as analytical concepts for understanding the past. What happens when different cultures, states and people meet, and what happens in and to the places and spaces where such meetings occur? These are among the questions that are elucidated in nine investigations that deal with several different examples from history, from the very concrete to the more metaphorical, and spanning macro to micro scales of study. The nine contributions range, in terms of time, from the transition from the Middle Ages to the early modern age at the beginning of the 16th century, up to our own era. Geographically, the investigations concentrate on three areas. One is the Nordic region: geographical and cultural contact zones are examined within and between the different Nordic countries. Several contributions deal with the period when Norway was part of a larger northern European composite state, Denmark-Norway. The second area is the Middle East. Here, both the royal court as a contact zone in the Ottoman Empire is discussed, as well as contact and conflict in the Kurdish border countries during the 2000s. The last area is the American Midwest. The chapters covering this region focus particularly on Norwegian immigrant communities in the United States, with detours to other parts of the world such as China and Troms in Norway. In all these time periods and geographical regions, the different encounters, contact and negotiations that took place between various actors and groups in both actual and metaphorical border areas are examined. This anthology originated with a research group in the Department of History at Volda University College and is also a tribute in honor of department's 50th anniversary. It is mainly aimed at researchers and students in history, but may also be of interest to those working related fields such as religion, sociology or legal history, or general readers interested in history and culture.